1995
DOI: 10.1093/geronb/50b.4.s259
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Nursing Home use through Community Long-Term Care: An Optimization Analysis

Abstract: Can community services be made more effective in reducing nursing home use through better management of their mix and allocation? To test this idea, we used data from the National Long-Term Care Channeling Demonstration to estimate logistic regression models relating the use of various types of community services to nursing home use. We then used these estimates to form an objective function for a mathematical optimization procedure which minimizes total expected population nursing home use as a function of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 5 publications
2
25
0
Order By: Relevance
“…Controlling for all of the explanatory and mediating factors reduces the differences between the top and the bottom income quintiles by 59 per cent for women and 78 per cent for men. The finding that income is inversely associated with the risk of admission to institutional care corresponds with the results of some earlier studies (Greene et al 1995;Mustard et al 1999;Himes et al 2000;Lakdawalla and Schoeni 2003), but differs from those of other studies that show that income has no independent effect (Garber and MaCurdy 1989;Speare et al 1991;Steinbach 1992;Tomiak et al 2000). This difference could be the result of one or more of various factors: different national practices in providing institutional care and other services for elderly people according to their socioeconomic or family status; different definitions of the income and control variables, especially health status; and different definitions, coverage, and attrition rates in the follow-up of admission to institutional care.…”
Section: A Summary Of the Main Results And Their Interpretationsupporting
confidence: 90%
See 2 more Smart Citations
“…Controlling for all of the explanatory and mediating factors reduces the differences between the top and the bottom income quintiles by 59 per cent for women and 78 per cent for men. The finding that income is inversely associated with the risk of admission to institutional care corresponds with the results of some earlier studies (Greene et al 1995;Mustard et al 1999;Himes et al 2000;Lakdawalla and Schoeni 2003), but differs from those of other studies that show that income has no independent effect (Garber and MaCurdy 1989;Speare et al 1991;Steinbach 1992;Tomiak et al 2000). This difference could be the result of one or more of various factors: different national practices in providing institutional care and other services for elderly people according to their socioeconomic or family status; different definitions of the income and control variables, especially health status; and different definitions, coverage, and attrition rates in the follow-up of admission to institutional care.…”
Section: A Summary Of the Main Results And Their Interpretationsupporting
confidence: 90%
“…In contrast, other studies indicate that this probability decreases as income rises, independently of baseline health and socio-demographic confounders. This effect has been found among older adults in Manitoba, Canada (Mustard et al 1999), and among older adults (Lakdawalla and Schoeni 2003) and chronically disabled older adults in the USA (Greene et al 1995). Himes et al (2000) also found similar indicative effects of income among the general older population in the USA and Germany, although the results were statistically significant only at the 10-per-cent level.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…A few studies suggest that adequate HCBSs might be able to extend the time that older adults can successfully remain in their homes and assist them in maintaining a good quality of life in familiar surroundings (Greene & Lovely, 1995;Jette, Tennstedt, & Crawford, 1995;Weissert & Lesnick, 1997). Nevertheless, the evidence is unclear as to whether HCBSs can fully substitute for nursing home care or significantly delay permanent nursing home admissions (Miller & Weissert, 2000).…”
mentioning
confidence: 99%
“…The percentage of home-or communitybased care users in our research was much lower than those reported in developed Western countries [20][21][22]. Community-based services are a recent phenomenon in Taiwan [23].…”
Section: Discussion and Policy Implicationsmentioning
confidence: 56%